The Effect of Competence, Time Budget Pressure and Professional Attitudes of Auditors on Internal Audit Quality With Role Conflict As a Moderating Variable - Nurmawanti, Sylvia; Lenggogeni, Lenggogeni; Yanti, Harti Budi (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the effect of competence, time budget pressure and professional  attitudes  of  Inspectorate  auditors  on  audit  quality  with  role  conflict  as  a moderating  variable.  The  population  in  this  study  were  all  functional  auditors  who worked  in  the  Banten  Province  Regional  Inspectorate  which  consisted  of  62  auditors. The sampling technique in this study was to use the census method. This technique was chosen because the researcher has a consideration that the total number of auditors at the Inspectorate  of  Banten  Province  is  still  relatively  small  and  can  be  used  as  a  sample entirely.  The  data  analysis  method  uses  descriptive  analysis  and  multiple  linear regression.  Based  on  the  results  of  this  study  indicate  that  competence,  time  budget pressure and professional attitudes of auditors have a positive effect on audit quality. In addition, role conflict is unable to moderate the relationship between competence, time budget pressure and professional attitudes of auditors with audit quality